Modelling, Simulation and Analysis of PHERB Powertrain - Norbakyah, J.S.; Salisa, A.R. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Popularity due to high fuel efficiency have made plug-in hybrid electric vehicles (PHEVs) gives a great transformation in reducing fuel consumption, fuel cost and gas emission. Marine transportation such as boat, ship, tanker, bulk carries, tow and tug also need the revolution replacing their diesel conventional with the hybrid electric vehicle. In this paper, plug-in hybrid electric recreational boat (PHERB) was presented. This research aims to present modelling and simulation of main powertrain PHERB based on a mathematical model in MATLAB/SIMULINK environment, in order to respond to power and speed through a drive cycle. The accuracy of the model is compared with advanced vehicle simulator (ADVISOR) software. The result of simulation main powertrain, fuel economy and emission of PHERB and ADVISOR model were compared, and the pro and con were discussed. This model can be used as a reference to build a hybrid electric boat in Malaysia environment.